Proteksi Pekerja Migran dalam Sengketa Perburuhan Ditinjau dari Undang-Undang No 6 Tahun 2012 tentang Pengesahan International Convention On The Protection Of The Rights Of All Migrant Workers And Members Of Their Families Tahun 1990 - Mohamad Yuflih Huda Maheswara; Andrea Monica Sari (CV Rewang Rencang, 2022)
The International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families provides protection for workers' rights that need to be harmonized with current developments. This convention guarantees respect and equality of position and status for migrant workers in the era of globalization. With the current urgency, the 1990 Migrant Convention which has been ratified into Law No. 6 of 2012 needs to be analyzed through normative legal studies so as to produce suggestions for optimizing some of the gaps in the 1990 Migrant Convention.